Determination of the datum temperature for applying maturity in cold weathers Determinación de la temperatura datum para la aplicación de la madurez en climas fríos - Ebensperger, L.; Oyarzún, J.; Torres, R. (My University, 2020)
The recently approved Chilean standard NCh3565 for the use of Concrete Maturity to estimate the Concrete Strength has greatly facilitated the technological transfer of new wireless measurement technologies with online connection (IoT), represented by the maturity sensors. In this sense, preliminary on field tests carried out on pavements incorporating sensors in the city of Punta Arenas made it possible to detect that the assignment of the value of the Datum Temperature to the fixed value of 0 °C does not deliver the real resistance results determined by means of control cylinders and concrete cores. This work deepens on this topic proposing as a conclusion the use of a variable value of Datum Temperature for cold climates.
Keywords: cold climate; concrete; datum temperature; maturity; pavements